Quality analysis of the near-infrared spectra of wheat samples - Kónya, Éva; Kovács, Géza; Győri, Zoltán (Acta Agraria Debreceniensis, 2012)
The near infrared spectroscopy is widely used in the different industries as a rapid, non-invasive analitical tool. It is suitable for identification, qualification and quantitative analysis as well. As this technique is indirect, to make accurate calibration equations we need a proper sample population. Before the quantitaive analysis, developing calibiration modells we have to collect and examine the spectra. In our study we examined wheat samples with known origins to find if there is any effect of the growing area on the NIR spectra.